Pengaruh Kualitas Pelayanan dan Harga Terhadap Loyalitas Konsumen Pada Global Motor Gorontalo - Badu, Nur Milawati Saputri (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This research aims to determine the effect of product, price, promotion, and location on purchasing decisions. The data used in the research are primary data sourced from filling out questionnaires. The sample used in the research amounted to 56 respondents with the form sampling using accidental. The analytical technique used to answer the research problem and test the hypothesis is multiple regression analysis using a statistical product service (SPSS) application which is used to analyze the data. The results of the research (1) there is a negative but not significant effect of the product on purchasing decisions (2) there is a positive and significant effect of price on purchasing decisions (3) there is a positive and significant influence of promotion on purchasing decisions (4) there is a positive but not significant influence of location on purchasing decisions (5) there is an effect of the product, price, promotion and location on purchasing decisions.